Oyster Farming Management - Fajrin, Mahmudin; Junianto (Aquaculture Department, University of Mataram, 2025)
Pacific oysters (Crassostrea gigas) are one of the major aquaculture commodities that contribute greatly to the Japanese fishing industry. This study aims to describe the oyster farming management system based on field research experience in Hyogo Prefecture, Japan. The method used was participatory observation for eight months, covering all stages of aquaculture from seed collection to post-harvest. Observations showed that oyster farming is carried out using the hanging raft method (ikada-suika-shiki), relying on natural food in the form of plankton with depth management and regular hanger rotation. A seed training process (yokusei) was also applied to increase the oyster's resistance to environmental stress. The growth rate of oysters in the rearing phase ranges from 0.25-0.35 grams per day, and harvesting is done during winter to produce high-quality meat. The implementation of efficient and systematic production management has proven to increase yield and product quality. These results suggest that oyster farming practices in Japan can serve as a reference in the development of sustainable oyster farming in Indonesia.